Giving greater financial independence to hospitals-does it make a difference? The case of English NHS Trusts - Marini, Giorgia; Miraldo, Marisa; Jacobs, Rowena; Goddard, Maria (Health economics, 2008)
In 2003 a new type of provider organisation, the Foundation Trust (FT), was introduced in England, and the best performing NHS hospitals were able to apply for ‘Foundation status’. FTs enjoy greater financial flexibility and are subject to less central monitoring and control. The phased introduction of FTs represents an opportunity to examine whether the new financial structures facing FTs have produced any differences in financial performance compared with non‐FTs. We use difference in difference methods to examine whether Foundation status had a significant effect on financial management. We find that Foundation status has had a limited impact in terms of acting as an instrument to signal strong financial management of FTs. This result may reflect the relatively early stage of the FT process or may be due to the fact that all types of Trusts are experiencing a challenging financial environment, including the introduction of a prospective payment system. However, we explore the nature of the trends emerging over time and discuss the implications of our findings for policy. Copyright © 2007 John Wiley & Sons, Ltd.